Pemanfaatan Alokasi Dana Desa Dalam Proses Pemberdayaan Masyarakat Desa (Study Pada Desa Puosu Kecamatan Benua Kabupaten Konawe Selatan) - Limbong, Teto; Qomariyah, Erni; Gunawan, Gunawan (Universitas Halu Oleo, 2020)
The problem formulation in this research is how the utilization of village funds allocation in the process of empowering the village community in the village Puosu subdistricts of South Konawe district. The research aims to use the allocation of village funds in the process of empowering village communities in the village Puosu Sub-district of South Konawe district. This research was conducted in the village Puosu subdistricts of South Konawe District, where the informant in this research is the head of village, chairman of BPD, Sekertaris Village, treasurer of the village, and five Stempat communities. The data analysis techniques in this study are using primary data and secondary data, the data collected will be analyzed qualitatively. The data collection techniques in this study are using methods of interviews, observations and documentation. The results showed that the utilization of village funds allocation in the process of empowerment of village community in Puosu Village Sub-district of South Konawe district is still said to be maximum. This has been disclosed by the informant, but the village chief continues to coordinate with the community to plan the appropriate programmes for the advancement of the village Puosu.